Study on Advancements in Neuromodulation - Jing Zhang (New Frontiers in Medicine and Medical Research Vol. 9, 2021)
Recent advancements in neuromodulation such as spinal cord stimulation and neuromuscular stimulation in spinal cord injury have made it possible for patients with complete paralysis to recover motor function. In this mini-review, these recent studies were reviewed, possible mechanisms of such motor recovery were analyzed, and ways to further improve neuromodulation for function restoration were outlined. In addition, since complete paralysis is usually incurable, the progress of recent neuromodulation studies in spinal cord injury opens up new possibilities that neuromodulation may treat other incurable diseases such as Parkinson’s disease, cerebral palsy, and multiple sclerosis. This mini-review further discussed perspectives to release the full potential of neuromodulation to achieve significant clinical effectiveness and reduce adverse effects in the reestablishment of physiological homeostasis in order to bring cure to patients with incurable diseases and relieve them from suffering.